GP88 Enhancing services for vulnerable children and families through public health nurses participation in a workforce capacity building initiative and interagency and partnership in a low-income irish community. (June 2019) - Buckley, Lynn; Curtin, Margaret; Maguire, Catherine; Walsh, Grace; Gibson, Louise; Harford, Katherine
Abstract : Background: The provision of high-quality support and care from pregnancy to age three can influence lifelong health and social outcomes. This is particularly the case for children born into intergenerational poverty. Evidence suggests that progressive, targeted-universal approaches are most effective in enhancing early development outcomes, particularly when delivered through community-based infant health and well-being services. In Ireland, Public Health Nurses (PHNs) provide the core nursing and midwifery care in the community working from a 'cradle to grave' model that span the lifecycle. This model requires PHNs to provide specialist early years support to vulnerable children and families within a largely generalist role.Additional training and engagement in innovative partnership can support PHNs to fulfil this role. Young Knocknaheeny (YK) is an interagency collaboration aiming to reduce child poverty and enhance child development (age 0 to 6) across four low-income Irish neighbourhoods. The programme is underpinned by an innovative Infant Mental Health (IMH) framework. Locally-based PHNs are key partners in YK and have engaged in a variety of initiatives. These included: an intensive IMH training and coaching programme; inter-disciplinary prevention and early intervention using an IMH framework, through a local KidScope paediatric clinic; working with YK Oral Language Officers to offer accessible speech, language and communication support to all parents with babies attending the 7 to 9 month developmental assessments (Babbling Babies clinic). Aims: The overall aim was to explore the impact of training, capacity-building and partnership working on services delivered by PHNs to vulnerable children and families. Methodology: This study formed part of a process evaluation of the YK programme undertaken between 2015 and 2017. A mixed methods approach was adopted. YK and KidScope administrative databases were analysed. Qualitative methods were used to gain PHNs perspectives on IMH training and their engagement with YK, Babbling Babies and KidScope . Results: Twenty-four PHNs participated in IMH training and on-going mentoring. 63% of children born in the area were seen at the Babbling Babies clinic. PHNs reported the IMH-informed 'common language' enhanced the quality of their interactions with community practitioners and with families. The partnership process further facilitated PHNs engagement with 'hard-to-reach' families. Discussion/Conclusion: The YK programme enhanced the capacity of PHNs to provide high-quality support to vulnerable families in the critical early years. The evaluation suggests that a shift in the current 'cradle to grave' PHN model towards a specialist early years PHN could improve health and well-being outcomes for children/families.